Kegiatan Lokakarya Perencanaan Berbasis Data Program Sekolah Penggerak Angkatan I Tahun Ketiga di Kabupaten Soppeng - Hamzah, Rahma Ashari (Politeknik Negeri Cilacap, 2024)
Data-based planning is the process of collecting, analyzing and using data to determine goals, strategies and activities that will be carried out to improve and increase the quality of education in schools which is very important to understand in the Driving School Program. The aim of this workshop activity is that participants who attend are able to prepare data-based plans which will later produce Annual Work Plans (RKT) and School Work Plans and Budgets (RKAS) which are part of data-based planning in schools. The method used in the form of a data-based planning workshop is participatory from the learning committee, namely the principal and elementary school teachers of each school, including from 4 levels of elementary school, namely SDN 100 Dare Bunga-Bungae, SDN 118 Ujung, SDN 238 Laempa, and SDN 5 Mattiropole in the area. Soppeng Regency. The data-based planning workshop activity was held on Saturday 11 November 2023 at SMPN 3 Watansoppeng by involving participants directly during the activity with a flow of activities starting from the opening, starting from the self, concept exploration, collaboration space, contextual demonstration, real action plan and closing. The final result of this data-based planning workshop activity is a draft product of the Annual Work Plan (RKT) and School Work Plan and Budget (RKAS). Thus, these data-based planning activities can have a positive impact on each school in the Class I Driving School Program, which can strengthen various participants' skills and competencies in preparing designs related to data-based planning, thereby encouraging digitalization in schools